2015
DOI: 10.1186/s13613-015-0099-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ICU-bed availability on ICU admission decisions

Abstract: BackgroundThe potential influence of bed availability on triage to intensive care unit (ICU) admission is among the factors that may influence the ideal ratio of ICU beds to population: thus, high bed availability (HBA) may result in the admission of patients too well or too sick to benefit, whereas bed scarcity may result in refusal of patients likely to benefit from ICU admission.MethodsCharacteristics and outcomes of patient admitted in four ICUs with usual HBA, defined by admission refusal rate less than 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 24 publications
(35 reference statements)
1
45
0
2
Order By: Relevance
“…Only a small portion of hospital beds are capable of critical care, and occupancy is high . Decreased ICU availability leads to downtriage of subsequent patients who may have substantial illness and who are shown to have increased mortality levels . Further, ICU admissions are costly: charges for 1 day in the ICU are three times greater than for 1 day on the general floor .…”
Section: Discussionmentioning
confidence: 99%
“…Only a small portion of hospital beds are capable of critical care, and occupancy is high . Decreased ICU availability leads to downtriage of subsequent patients who may have substantial illness and who are shown to have increased mortality levels . Further, ICU admissions are costly: charges for 1 day in the ICU are three times greater than for 1 day on the general floor .…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the preponderance of evidence suggests that ICU clinicians allocate intensive care services inefficiently as increased ICU bed availability leads to ICU care for those who may not need it. Several studies demonstrate a clear association between the number of available ICU beds and the likelihood that a patient will be admitted to an ICU [13,14]. For example, one study revealed that ICU's with high bed availability were much more likely to admit patients who were either too sick or too healthy to benefit from ICU care than ICU's with limited bed availability [13].…”
Section: #2 "Many People Take No Care Of Their Money Till They Come mentioning
confidence: 99%
“…Several studies demonstrate a clear association between the number of available ICU beds and the likelihood that a patient will be admitted to an ICU [13,14]. For example, one study revealed that ICU's with high bed availability were much more likely to admit patients who were either too sick or too healthy to benefit from ICU care than ICU's with limited bed availability [13]. The abundance of ICU beds has led to indiscriminate use of ICU care-where critically ill and non-critically ill patients are granted ICU access in a first-come, first-served model until ICU beds become limited.…”
Section: #2 "Many People Take No Care Of Their Money Till They Come mentioning
confidence: 99%
“…On the other hand, too much of a good thing is not necessarily better. When Robert et al compared ICUs with usually high bed availability versus those with low bed availability, they observed that availability of more beds was associated with significantly more frequent admission of patients who were less likely to benefit from ICU care (those too well, or too sick to benefit) (6). Perhaps this is a reflection of human nature that when a resource is limited, we would think twice before utilizing it.…”
mentioning
confidence: 99%